The philosophy of transhumanism : a critical analysis - Ross, Benjamin (Emerald Publishing Limited, 2020)
Transhumanism is an international movement which anticipates humans developing posthuman capacities in the near future. This work provides an introduction to transhumanism and the ethical and philosophical issues raised by radical human enhancement. The book investigates these questions in a way that is timely and accessible to the non-specialist.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Transhumanism -- Philosophy; Philosophy, Mind & Body; Philosophy: metaphysics & ontology